Análise de modelos de estimativa da concentração de clorofila-a, utilizando dados de sensoriamento remoto - Mendonça, Janaina Castro de (2016)
The surface reservoirs in the State of Ceará are responsible for supplying the population in many activities. On the context, the monitoring of these reservoirs should be done efficiently, in order to preserve a scarce resource, which is limited quantitatively, but also qualitatively. Thus, this study aimed to analyze the use of remote sensing as an alternative to monitoring water quality and analyze models that estimate the chlorophyll-a concentrations in reservoir of the semiarid region in the state of Ceará. Field samples were carried out in the Pereira de Miranda reservoir, located in Pentecoste, State of Ceará, Brazil. Five sampling points was analyzed from December 2014 to December 2015. Therefore, limnology data were used. Water samples were collected in bottles of 1L and spectral data were collected with a spectroradiometer. For the analysis and application of models to estimate the concentrations of chlorophyll-a limnology attributes of chlorophyll-a and total suspended solids were analyzed in the laboratory. They were used to evaluate the spectral responses of water too. These effects were observed in the limnological attributes in the reflectance curves as well as the trophic status of the reservoir. Four models of three bands were analyzed to estimate the concentrations of chlorophyll-a, between them, the both models that performed best were Lopes (2013), with studies conducted in the semiarid region of northeastern Brazil, with values of R² = 0 75, NSE = 0.74 and EMA = 6.74 ug L-1 and Gitelson et al. (2007) that studies in estuaries of Chesapeake Bay, United States, with R ² = 0.79, NSE = 0.74 and EMA = 6.51 ug L-1. According these results these both models were selected for use with sample data of April and September 2015. The models showed satisfactory results, but depending on the model and the point sample, the values have overestimated or underestimated concentrations, This results indicate that it is necessary adjustments in the spectral bands for applications in this semiarid region. Therefore, the use of remote sensing is feasible to estimate the concentrations of chlorophyll-a. The remote sensing contributes to the development of research and management of water resources in lower cost, and it generates useful information to decision-making by managers.